Disturbed body perception, reduced sleep, and kinesiophobia in subjects with pregnancy-related persistent lumbopelvic pain and moderate levels of disability: An exploratory study - Beales, Darren; Lutz, A.; Thompson, Judith; Wand, B.; O'Sullivan, Peter (Churchill Livingstone, 2014)
Background: For a small but significant group, pregnancy-related lumbopelvic pain may become persistent. While multiple factors may contribute to disability in this group, previous studies have not investigated sleep impairments, body perception or mindfulness as potential factors associated with disability post-partum. Objectives: To compare women experiencing no pain post-pregnancy with those experiencing pregnancy-related persistent lumbopelvic pain (either low- or high-level disability) across multiple biopsychosocial domains. Design Cross-sectional. Methods: Participants completed questionnaires for thorough profiling of factors thought to be important in pregnancy-related lumbopelvic pain. Specific measures were the Urinary Distress Inventory, Medical Outcomes Study Sleep Scale, Back Beliefs Questionnaire, Tampa Scale for Kinesiophobia, Depression Anxiety Stress Scale, Coping Strategies Questionnaire, Pain Catastrophising Scale, The Fremantle Back Awareness Questionnaire and the Mindful Attention Awareness Scale. Women where categorised into three groups; pain free (n = 26), mild disability (n = 12) and moderate disability (n = 12) (based on Oswestry Disability Index scores). Non-parametric group comparisons were used to compare groups across the profiling variables. Results: Differences were identified for kinesiophobia (p = 0.03), body perception (p = 0.02), sleep quantity (p < 0.01) and sleep adequacy (p = 0.02). Generally subjects in the moderate disability group had more negative findings for these variables.Conclusion: Disturbances in body-perception, sleep and elevated kinesiophobia were found in pregnancy-related lumbopelvic pain subjects with moderate disability, factors previously linked to persistent low back pain. The cross-sectional nature of this study does not allow for identification of directional pathways between factors. The results support the consideration of these factors in the assessment and management of pregnancy-related lumbopelvic pain.